PROGRAM BANTUAN PERUMAHAN LAYAK HUNI BAGI MASYARAKAT DAERAH ALIRAN SUNGAI DI DESA KUALA TERUSAN KABUPATEN PELALAWAN (SUATU ANALISIS PENDEKATAN PEMBANGUNAN) - Satria Rahmaddan; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research carried out in the Village Kuala Terusan Pelalawan Regency. The purpose of this research is to analyze the aspirations of the Village Kuala Terusan against the help of the housing worth living in accordance with the needs of. The focus of this study is the development of the use of the goverment in objectify program help housing worth living given to the public. This study using a quantitative analysis of the descriptive and set a sample of as munch 50 People Head Family (HF) using a method random sampling and instrumen data is inquiries or kuisioner, the interview, observations, and the documentation.Research conducted, the authors found that the development that carried out of the goverment in the help of the housing worth living in the Village Kuala Terusan using the concept of the development of Top-Down (from the top to bottom). Where planning carried out by the government as the default the idea of as well as the government to act more dominant in set the program that originated from, the process of planning to evaluation, the role of people don’t be involved. The aspirations of the people of the help of the housing worth living, the aspirations againts the location; the location that is not far from the river, but not to be in the low. The aspirations of the respondents againts the form of the house; the form of house type the stage. The aspirations of the respondents againts the facility; the facility as well, the bathroom, and shelters water.Keywords: The help program, approach reconstruction, aspirations